Authority, Autonomy, and the Archaeology of a Mississippian Community : Nature's Economic and Ecological Wealth - Nelson, Erin S. (Book collections on Project MUSE., 2020)
This book is the first detailed investigation of the important archaeological site of Parchman Place in the Mississippi Delta, a defining area for understanding the Mississippian culture that spanned much of what is now the United States Southeast and Midwest before the fifteenth century.